Pembuatan Aplikasi Sistem Informasi Administrasi dan Manajemen Proyek pada CV. SQUAD - Defta Jayesena Valrisano; Djoni Haryadi Setiabudi; Rudy Adipranata (Jurnal Infra, 2016)
CV. Squad is a company that work on specialist termite and pest control. This company wish to replacing the old system with computerization, because they had a difficulty in dealing with administrative issues because its operation is still manual, e.g. the sales and work schedule. Thus allow for errors in the financial calculation. From the background of these problems, we designed a application that support performance and set project management on CV. Squad. This system is built using PHP as programmer language and MySQL for the database.The results obtained from this application can take notes of purchasing transactions and sales can be done according to the structure and computerize and also complemented with stock card using First In First Out (FIFO) method. Each project also became more structured with monitoring feature on project management. Otherwise, with this application, owner can know some reports like stock report, debt, account receivable report and income statement.